Civilian Missile Injuries in Iraq after 2003, Misan as an Example - Haithem Abd Al-Khazrajee (Indian Journal of Forensic Medicine & Toxicology, 2021)
A retrospective study analyzing data of patients admitted because of missile injuries over more than onedecade in Misan, Iraq.4098 patients were involved in the study, 3550 patients sustained bullet injuries and 548patients sustained explosive injuries. Urban young male patients were mainly affected. Periods of politicalinstability and civilian unrest were associated with increasing numbers of affected patients especially theyears (2003-2007) and (2014-2015). Fatal injuries were due to bullet injuries rather than explosive injuries.In conclusions effective legislations regulating the use of weapon in the civilian life, political stability, andinternational supports are important factors that help the country to reduce the effect of this problem.